Living and working in Europe. Yearbook 2009 (Dublin, 2010)
"The European Union, together with its citizens, is undergoing profound change. Demographic change, greater global competition, technological developments and the enlargement of the EU itself are all shaping the lives – both private and professional – of ordinary men and women across the Member States. This overview uses Eurofound’s research findings to capture a snapshot of what it means to live and work in Europe at the start of the 21st century. The reports listed in this overview, all available through the Eurofound website, will give the reader a deeper insight into the issues raised here."